2005
DOI: 10.1128/iai.73.6.3714-3724.2005
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Genes Encoding Innate Host Defense Molecules in Normal Human Monocytes in Response toCandida albicans

Abstract: Little is known about the regulation and coordinated expression of genes involved in the innate host response to Candida albicans. We therefore examined the kinetic profile of gene expression of innate host defense molecules in normal human monocytes infected with C. albicans using microarray technology. Freshly isolated peripheral blood monocytes from five healthy donors were incubated with C. albicans for 0 to 18 h in parallel with time-matched uninfected control cells. RNA from monocytes was extracted and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 61 publications
(46 reference statements)
4
49
0
Order By: Relevance
“…A number of studies has shown the important role of IL-1 and IL-1Rs in resistance to candidiasis (38,39,46). However, through different immune mechanisms, both IL-1␣ and IL-1␤, produced through transcription and translation by the host (47), are involved in host defense against the fungus and contribute to the production of IFN-␥ (39).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies has shown the important role of IL-1 and IL-1Rs in resistance to candidiasis (38,39,46). However, through different immune mechanisms, both IL-1␣ and IL-1␤, produced through transcription and translation by the host (47), are involved in host defense against the fungus and contribute to the production of IFN-␥ (39).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages, neutrophils and peripheral blood mononuclear cells (PBMCs) respond to a broad range of microbial stimuli with common transcriptional activation programmes [32,36,50]. In this regard, microarray analyses have shown an increase of genes related to innate immunity in macrophages infected with Mycobacterium tuberculosis, C. albicans and A. fumigatus [35,36,51]. Recently, for the first time, Silva et al (in press) [52] used cDNA microarray analysis to identify differential genes of macrophages infected with P. brasiliensis that are related to several immune processes such as inflammation, cell membrane regulation, transcriptional regulation, signal transduction, and apoptosis.…”
Section: Transcriptional Response Of Macrophage Cells Upon Infection mentioning
confidence: 99%
“…In recent years, several approaches such as cDNA microarrays, cDNA representational difference analysis (RDA) and serial analysis of gene expression (SAGE) have been developed to identify general profiles of gene expression [32,33]. Specifically, the cDNA microarray technology has been applied to the analysis of bacterial and fungal interactions with phagocytes, thus identifying key effectors of pathogen virulence and host defence [32,[34][35][36].…”
Section: Global Patterns Of Gene Expression In the Host-pathogen Intementioning
confidence: 99%
See 1 more Smart Citation
“…Candida albicans infection in a murine intravenous challenge model situation occurring in the affected organs undergoing C. albicans infection (8)(9)(10). Therefore, the aim of the present study was to assess the local cytokine production in various organs (spleen, kidney and brain) during systemic C. albicans infection, as local cytokine levels and activity are of considerably greater value for monitoring the pathological events in a target tissue, rather than systemic cytokine levels (11).…”
Section: Early Expression Of Local Cytokines During Systemicmentioning
confidence: 99%